SCREENING OF ANTIPYRETIC ACTIVITY OF METHANOL EXTRACT OF GRACILARIA CORTICATA J.AG. (RED SEAWEED) IN HARE ISLAND, THOOTHUKUDI, TAMIL NADU, INDIA - J., John Peter Paul (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To investigate the antipyretic activity of methanol extract of Gracilaria corticata J.Ag. collected from Hare island, Thoothukudi in the south east coast of Tamil Nadu, India. Methods: Antipyretic activity was determined by brewer's yeast induced pyrexia method. Dried powder plant materials were subjected to methanol extract at the dose of 200mg/kg and 400mg/kg body weight. Results: Methanol extract showed potential significant antipyretic activity in both doses (p<0.001 and p<0.01) from 1 hour to 4 hour as compared to the standard drug paracetamol. Conclusion: The present study has been provided the evidence for the antipyretic activity of Gracilaria corticata J.Ag. which could partly contribute to its ethno medical use.